Competências e habilidades necessárias aos gestores na implementação da pedagogia de projetos - Almeida, Neusa Aparecida Basso de (2007)
The life, in full sense, is associated always to capacities to project. The educations looks for new foundations to build trough innovative curricula. The present work has as objective, through a case study and bibliographical research to promote a contextualizes reflection concerning the Competences and Necessary Abilities to the Managers to the Implementation of the Pedagogy of Projects, in a Public School of the State of São Paulo, Management of Teaching of Birigui. Assisting the objectives or Unesco (to redirect the educational work), and the objectives of the Constitution (the citizen s formation) more citizen and solidary, they implemented in all the components curriculares the Pedagogy of Projects, developing the citizenship project. The theme was investigated starting from collected data, through semi-structured interviews, analysis of relative documents to the organization of the school for projects, to the profile and participants expectation in relation to the Pedagogy of Projects and the School Administration. The interviews were accomplished with seven educational educators and three educantor managers (Director, Vice-Director and Pedagogic Coordinating Teacher), all with basic day or work and they work there is more than four years in this unit. For the accomplishment of this study, we looked for theorical fundamentation to the light or the studies of Hernández, Machado, Nogueira, Thurler, Ferreira, Valérien, Santos, Luck and other as for the Pedagogy of Projects, School Administration, Competences and Abilities and Innovation and Change in the Education.Like this, the studies pointed to investigate among the competences: Interpessoais, Technician-Political-Pedagogic and Partner-Cultural and their respectives abilities, the most necessary to the educators managers to implement the Pedagogy of Projects in the school curriculum. This action project seeks educator s trans-formation and students for believing that the construction of the citizenship travels a road with the identify formation, self-esteem, coexistence and solidarity.